DIGITALISASI PENINGGALAN CAGAR BUDAYA DI DESA NGRAWAN SEBAGAI UPAYA PELESTARIAN WARISAN BUDAYA - Nugroho, Listyanto Aji; Wuryani, Emy (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2024)
Community service program in Ngrawan hamlet, Ngrawan village, Getasan sub-district, Semarang regency is designed with a holistic approach involving the strategies of seminars, training, practical exercises, and mentoring. The program's location is chosen to enhance community understanding and engagement with cultural heritage remains. Program evaluation is conducted through pre-tests and post-tests during seminars to measure participants' understanding achievements. At the end of the activities, a comprehensive evaluation is performed on the training products, such as digitalization SOP for cultural heritage, documentation, and digitalization results (360° photos and video profiles of cultural heritage objects). The evaluation results serve as a foundation to ensure the sustainability of the program, including the possibility of mentoring for local partner organizations. The program aims to have a positive impact on preserving local cultural heritage and increasing community participation in the process.